Cytotoxic compounds from marine actinomycetes: sources, structures and bioactivity - Ziyan Qiu; Yinshuang Wu; Kunyan Lan; Shiyi Wang; Huilin Yu; Yufei Wang; Cong Wang; Shugeng Cao (Compuscript Ltd, 2022)
Marine actinomycetes produce a substantial number of natural products with cytotoxic activity. Actinomycete strains have been isolated from sources including fishes, coral, sponges, seaweeds, mangroves and sediments. These cytotoxic compounds can be broadly categorized into four classes: polyketides; non-ribosomal peptides and hybrids; isoprenoids and hybrids; and others, among which the majority are polyketides (146 of 254). Twenty-two of the 254 compounds show potent cytotoxicity, with IC50 values at the ng/mL or nM level. This review highlights the sources, structures and antitumor activity of 254 natural products isolated from marine actinomycetes and first reported between 1989 and 2020.